The impact of coronary revascularization on vessel-specific coronary flow capacity and long-term outcomes: a serial [15O]H2O positron emission tomography perfusion imaging study. (8th December 2021) - de Winter, Ruben W; Jukema, Ruurt A; van Diemen, Pepijn A; Schumacher, Stefan P; Driessen, Roel S; Stuijfzand, Wynand J; Everaars, Henk; Bom, Michiel J; van Rossum, Albert C; van de Ven, Peter M; Verouden, Niels J; Nap, Alexander; et al.
Abstract: Aims: Coronary flow capacity (CFC) integrates quantitative hyperaemic myocardial blood flow (hMBF) and coronary flow reserve (CFR) to comprehensively assess physiological severity of coronary artery disease (CAD). This study evaluated the effects of revascularization on CFC as assessed by serial [ 15 O]H2 O positron emission tomography (PET) perfusion imaging. Methods and results: A total of 314 patients with stable CAD underwent [ 15 O]H2 O PET imaging at baseline and after myocardial revascularization to assess changes in hMBF, CFR, and CFC in 415 revascularized vessels. Using thresholds for ischaemia and normal perfusion, vessels were stratified in five CFC categories: myocardial steal, severely reduced CFC, moderately reduced CFC, minimally reduced CFC, and normal flow. Additionally, the association between CFC increase and the composite endpoint of death and non-fatal myocardial infarction (MI) was studied. Vessel-specific CFC improved after revascularization ( P < 0.01). Furthermore, baseline CFC was an independent predictor of CFC increase ( P < 0.01). The largest changes in ΔhMBF (0.90 ± 0.74, 0.93 ± 0.65, 0.79 ± 0.74, 0.48 ± 0.61, and 0.29 ± 0.66 mL/min/g) and ΔCFR (1.01 ± 0.88, 0.99 ± 0.69, 0.87 ± 0.88, 0.66 ± 0.91, and −0.01 ± 1.06) were observed in vessels with lower baseline CFC ( P < 0.01 for both). During a median follow-up of 3.5 (95% CI 3.1–3.9) years, an increase in CFC was independently associated with lower rates of death and non-fatal MI (HR 0.43, 95% CI 0.19–0.98, P = 0.04). Conclusion: Successful revascularization results in an increase in CFC. Furthermore, baseline CFC was an independent predictor of change in hMBF, CFR, and subsequently CFC. In addition, an increase in CFC was associated with a favourable outcome in terms of death and non-fatal MI. Graphical Abstract: